IMPLEMENTASI MEDIA PEMBELAJARAN COA INTERAKTIF UNTUK MENINGKATKAN LITERASI AKUNTANSI SISWA SMK PGRI 2 CIMAHI - Riani Tanjung; Mohamad Nurkamal Fauzan; Surya Ramadhan Noor (Universitas Merdeka Madiun, 2026)
This community service program aims to enhance students’ accounting literacy through the implementation of interactive learning media combining game-based and digital applications, namely COA Quartet and Easy COA. The program was conducted at SMK PGRI 2 Cimahi involving 103 students from the Accounting and Financial Institution Department. The activity consisted of several stages: socialization, training, implementation of learning media, and evaluation through pre-test and post-test assessments. The results indicate a significant improvement in students’ conceptual understanding and practical ability to identify and classify accounting accounts. The average score increased from 61 in the pre-test to 84 in the post-test, while the standard deviation decreased from 9 to 6, reflecting a more even distribution of student achievement. Beyond cognitive gains, the program fostered accounting literacy through collaborative, engaging, and interactive learning experiences. Therefore, COA Quartet and Easy COA are proven to be effective and suitable for integration into accounting instruction at the vocational school level.